Feminism Analysis of Judges' Considerations for Post-Divorce Domestic Violence Victims in Medan and Banda Aceh Religious Courts - Yusuf, Nasruddin; Azizah, Nur; Hasan, Faradila (Universitas Islam Negeri Raden Intan Lampung, 2023)
Domestic violence (KDRT) often arises in a marriage, which then encourages the wife to sue her husband for divorce through the courts. In this case, the Compilation of Islamic Law (KHI) does not regulate the rights of a wife who sues her husband for divorce to obtain 'iddah, or mut'ah support. But the rules regarding this are in Book II of the Guidelines for Religious Courts and SEMA. This research is field research with a qualitative-comparative approach through a feminist perspective. The aim is to analyze the considerations of judges in deciding cases of divorce due to domestic violence in the Medan Religious Court and the Banda Aceh Sharia Court. The research found the fact that the considerations of judges in the Medan Religious Court when deciding cases of divorce due to domestic violence, do not consider the issue of 'iddah or mut'ah maintenance rights to the plaintiff (ex-wife) because this is not regulated in the KHI. This research concludes that, if analyzed from a feminist perspective, the decisions of the judges of the Medan Religious Court and the Banda Aceh Sharia Court tend to be unfair and discriminatory towards women. the principle of gender equality, where the law discriminates between the legal effects of divorce by the husband's will (talak) and divorce by the wife's will (divorce). Therefore, this research recommends that judges when deciding on a domestic violence case should not only adhere to one KHI but also consider other rules relevant to it.